Impact of Simulation on MRI Physicists (The International Journal for Scientific Research, 2023)
MRI is a very complex imaging modality in radiography. Although some simulators have been developed for training purposes, we are not sure about any of them. In this research, we tried to measure the performance of different simulations for educational purposes and then quantitatively evaluate them. With this paper, our study deals with an evaluative review of previous studies related to MRI simulators, which are designed to perform specific functions to help the medical engineer managing radiographic operations to better learn the theoretical and practical concepts of MRI from others. Traditional education, which is a method based on reviewing previous studies, searching for strengths and weaknesses in simulators and possible alternatives to them, and then providing recommendations for future studies that can be conducted to switch to packaging simulation programs, which are virtual laboratories that we hope will be the most efficient simulation devices and models used. Currently in MRI engineer qualification.
Keywords: C++; C; CUDA; Java; Krubach's Alpha Method; Bloch Equations; Fourier Transforms